Board of Directors, Audit Committee Characteristics and Performance of Nepalese Commercial Banks - Rana, Ishwari; Poudel, Garima; Chauhan, Jyoti; Panta, Jyoti; Pradhan, Sumit (Nepalese Journal of Economics, 2025)
The study examines the effect of board of directors and audit committee characteristics on the performance of Nepalese commercial banks. The dependent variables selected for the study are return on assets and earnings per share. The selected independent variables are board size, gender diversity, independent directors, audit committee size, total assets and number of board meetings. The study is based on secondary data of 11 commercial banks with 110 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of board of directors and audit committee characteristics on the performance of Nepalese commercial banks. The study showed that board size has a positive effect on return on assets and earnings per share. It means that higher the number of directors on the board, higher would be the return on assets and earnings per share. Similarly, gender diversity has a negative effect on return on assets and earnings per share. It means that increase in proportion female directors on board leads to decrease in return on assets and earnings per share. The results of the study also shows that audit committee has a positive effect on return on assets and earnings per share. It implies that larger the size of audit committee, higher would be the return on assets and earnings per share. Likewise, number of board meetings has a negative effect on return on assets and earnings per share which indicates that increase in the number of board meetings leads to decrease in return on assets and earnings per share. However, independent director has a negative effect on return on assets and earnings per share. It indicates that increase in number of independent directors on the board leads to decrease in return on assets and earnings per share. Similarly, total assets have a negative effect on return on assets and earnings per share. It implies that increase in total assets of the bank leads to decrease in return on assets and earnings per share.